(untitled) (Journal of actual problems of jurisprudence, 2016)
This article is devoted to the third stage of formation and development of the constitutional legislative of the Kazakhstan, which includes the period – 1990-1993years. Accordingly, in the article considers the content of the constitutional and legal acts adopted in this period, and also consider their analyzes. In conclusion about the meaning and role of the constitutional legislative of the Kazakhstan adopted in this period, which became the basis for the formation and development of the constitutional legislative of the sovereign and independent of Republic of the Kazakhstan.